Equilibrium and kinetic study on chromium (VI) removal from simulated waste water using gooseberry seeds as a novel biosorbent - J. Aravind; G. Sudha;; P. Kanmani; A.J. Devisri; S. Dhivyalakshmi; M. Raghavprasad (Global Journal of Environmental Science and Management)
Gooseberry seed (Phyllanthus acidus) was used as an adsorbent to determine its feasibility for the removal of Cr(VI). Various parameters such as pH, temperature, contact time, initial metal concentration and adsorbent dosage were investigated to determine the biosorption performance. Equilibrium was attained within 60 minutes and maximum removal of 96% was achieved under the optimum conditions at pH 2. The adsorption phenomenon demonstrated here was monolayer represented by Langmuir isotherm with R2 value of 0.992 and the Langmuir constants k and q0 was found to be 0.0061 (L/mg) and 19.23 (mg/g). The adsorption system obeyed Pseudo second order kinetics with R2 value of 0.999. The results of the present study indicated that gooseberry seed powder can be employed as adsorbent for the effective removal of hexavalent chromium economically.